Defining Proximity Levels between Kipchak Languages in Comparison to Finno-Ugric Ones: Analyses of Eighteenth-Century Dictionaries - Julia V. Normanskaja (Oriental Studies, 2023)
Introduction. Currently, researchers have no consensus on the classification of the Kipchak languages. The dictionaries compiled by P. S. Pallas provide valuable insights into the 18th-century Tatar, Bashkir, Nogai, and Kazakh languages. Goals. This article attempts an analysis of the latter’s graphic features in order to enhance our understanding of the development of dialect-classifying graphophonic isoglosses. Materials and methods. The paper examines the sixteen isoglosses identified by A. V. Dybo based on materials from modern Tatar, Bashkir, Kazakh and Nogai, and shows how numbers of common isoglosses for these languages differed in the 18th century. The dictionaries of P. S. Pallas have been uploaded to the online LingvoDoc platform, all words in these dictionaries now have parallels with modern literary languages, and with Turkic proto-forms according to EDAL. The dictionaries are also linked together by etymological connections. Results. The analysis shows that in the 18th century the languages were approximately equidistant from each other, some specific closeness observed just between Tatar and Bashkir, though Bashkir-Kazakh parallels differ by one innovation only, and no specific proximity between Kazakh and Nogai observed. It can be assumed that 20th-century communication resulted in a secondary convergence of Kazakh with Nogai and their common distancing from Tatar and Bashkir, the latter’s speakers in turn having become closer to each other. It is interesting to note that in 18th-century Bashkir and Nogai other archaic reflexes were represented, in particular, *s (Bashkir), *č (Nogai, Bashkir), *ƛ (š Nogai), these changes have occurred later. Conclusions. Thus, the analysis of the vocabularies created in the 18th century casts doubt on the traditional classification of N. Baskakov, A. Samoylovich, K. Musaev, and A. Savelyev based on the modern languages. At the same time, it should be noted that A. Dybo and O. Mudrak turned to glottochronology and applied morphological linguostatistics to have concluded together as to the specific proximity of Kazakh and Nogai, which is also not confirmed by the data of the graphics of the 18th-century texts.